Pore measurements on moraine topsoils using Computed Tomography which were sampled at Sustenpass and Klausenpass in the Swiss Alps in 2017 - Alessandra Musso; Krzysztof Lamorski; Markus Egli (PANGAEA, 2020)
The sampling campaign took place in August/September 2017 as part of the project HILLSCAPE, Hillslope Chronosequence and Process Evolution. This dataset comprises different pore parameters measured by Computed Tomography. Parameters of the pores include volume, radius, area and equivalent diameter. The Skeleton files include graph, segment and node statistics.